SAT0131 A Look To The Wrong Diagnosis of Rheumatoid Arthritis. (15th July 2016) - Palacio, N.; Buitrago-Garcia, D.; Castro, C.; Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; et al.
Abstract : Background: There is a lack of expertise in rheumatoid arthritis (RA) diagnosis in primary level of Colombian medical centers, leading to misdiagnosis; many times osteoarthritis (OA) and another rheumatic diseases are misdiagnosed as RA which derives in wrong treatment for patients with clinical and health economics implications. Objectives: The aim of this study was to describe demographic and clinical characteristics of a cohort of patients with misdiagnosis of RA in a specialized center in Colombia. Methods: A descriptive, cross sectional study. Were included patients who were referred from primary care centers to a RA specialized center in a 48 month period with presumptive diagnosis of this disease. Each patient was evaluated to confirm or rule-out diagnosis of RA as follows: a rheumatologist fulfilled a complete medical record including all previous data; it was assessed rheumatoid factor and anti-citrullinated antibodies, and other laboratories depending on each case. Also were made x-rays of hands and feet, and in some cases of persistent doubt about the diagnosis was requested comparative MRI of hands or/and feet. Frequencies and percentages were calculated for the demographic and clinical characteristics of the cohort of patients in which the diagnosis of RA was ruled-out. Results: In 5176 patients was found a wrong diagnosis of RA. Of these misdiagnosed patients, 4.385 (85%) were women, and 791 (15%) men, with an average age of 59 ± 13 years old. Between differential diagnosis which were found in this cohort of misdiagnosed patients: osteoarthritis in 2930 patients (56.6%), systemic lupus erythematosus (SLE) in 369 patients (7.1%), Sjögren syndrome in 237 patients (4.6%), spondyloarthropathies in 135 patients (2.6%), gout in 95 patients (1.8%), and in 28.3% of cases other diagnoses including all kinds of soft tissue rheumatism. Conclusions: Almost half patients with presumptive RA diagnosis in primary care centers in Colombia are misdiagnosed. The most important cofounding diagnosis was osteoarthritis and many patients were receiving DMARDs for treatment. For this reason there is an urgent need of education strategies for primary care physicians and the implementation of centers of excellence in RA, in order to conduct a proper diagnose and avoid clinical and health economics consequences of misdiagnosis. Disclosure of Interest: None declared